Non‐oxidative Dehydrogenation of Methanol to Formaldehyde over Bulk β‐Ga2O3. Issue 13 (9th May 2022) - Merko, Mariia; Busser, G. Wilma; Muhler, Martin
Abstract: The non‐oxidative dehydrogenation of methanol to formaldehyde is considered a dream reaction compared with the classical oxidative route, because the valuable coupled product hydrogen is formed instead of water, and the produced anhydrous formaldehyde is highly suitable for the further synthesis of oxygenated synthetic fuels. This study reports on the high catalytic performance of pure β‐Ga2 O3 in this reaction at temperatures between 500 °C and 650 °C. At 550 °C and a GHSV of 45500 h −1, an initial selectivity to formaldehyde of 77 % was obtained at a methanol conversion of 72 %. Performing the reaction at temperatures beyond this range and lower GHSV resulted in a lower formaldehyde selectivity. The catalyst suffered from deactivation caused by formation of carbon deposits, but it was possible to regenerate its initial activity at 500 °C and 550 °C completely by an oxidative treatment. Irreversible deactivation occurred at 650 °C due to partial volatilization of Ga2 O3 . Abstract : "GA" instead of "AG" : The application of Ga2 O3 in the non‐oxidative dehydrogenation of methanol to produce water‐free formaldehyde and hydrogen was established as a possible alternative to the classical oxidative dehydrogenation of methanol over Ag. In the temperature range from 500 °C to 650 °C dehydrogenation prevails the dehydration pathway over Ga2 O3, which can be fully oxidatively regenerated at 500 °C and 550 °C.